การวิเคราะห์ผลกระทบของปัจจัยเสี่ยงต่อระยะเวลาก่อนสร้างถนน - วรุณ สถิรวุฒิพงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The objective of this thesis is to analyze the effect of several risk factors on duration time in highway construction and related activities. The analysis was used in estimating duration time corresponding to precictable risk condition in highway project planning stage. In preliminary study, impact level of risk factors on duration time in highway activities were ranked by both highway contractors and senior engineers of the Department of Highways (DOH) through questionnaires and interviews. The survey result indicates that rain is the major factor affecting duration time of earthwork, subbase, base, and surface construction. The report from the Meteorological Department shows that there are 90 and 120 rainy days in provinces which have rainfall less than and more than 1500 mm respectively. Apart from rain factor, other factors that have high impact on duration time are earthwork-related tasks. These factors include soil condition, proprietary right of land, and relocation of utility system. The additional time needed when these factors were applied was calculated from the fuzzy membership function constructed from the survey result. Proposed risk assessment form was used alorg with modified traditional method of estimating the duration time of the construction to verify the constructed membership functions by comparing the estimated and actual duration time of seven delayed projects coping with risk factors during construction. The result shows that average errors of estimated earthwork and project duration time are 9.13% and 12.23% respectively which are less than errors from traditional method. Thus, the proposed method can serve as a risk assessment guideline for planning construction time. It can help minimizing the impact from underestimating the duration time especially in project dealing with risk factors.